Development of smart glasses using an infrared distance measurement sensor - Kang, Jaeyoung; Kim, Da Ran; Na, Kyung-Sun; Kim, Dae Yu (2023 IEEE International Conference on Consumer Electronics-Asia (ICCE-Asia), 2023)
This study provides methods of measuring the distance between the human eye and an object using an infrared distance sensor. The method provides a smart way to monitor subjects near or far vision over time using the smart device before cataract surgery. An Arduino board-based infrared distance sensor on the rim of smart glasses can measure a range of 20.00 to 80.00 centimeters as well as detect the distance from the smart glass to objects at 4 times per second.